2004 Kansas Performance Tests with Corn Hybrids - Roozeboom, Kraig L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Corn performance tests, conducted annually by the Kansas Agricultural Experiment Station, provide farmers, extension workers, and seed industry personnel with unbiased agronomic information on many of the corn hybrids marketed in the state. Because entry selection and location are voluntary, not all hybrids grown in the state are included in tests, and the same group of hybrids is not grown uniformly at all test locations.
Keywords: Corn; Yields; Kansas; Disease; Weather; Insects; Statistics